Clinical significance of the CD98hc-CD147 complex in ovarian cancer: a bioinformatics analysis - Xin-Yue Zhou; Jin-Yao Li; Jing-Tong Tan; Yi-Li HuangLi; Xiao-Cui Nie; Pu Xia (Taylor & Francis Group, 2023)
Ovarian cancer is one of the most common malignant tumours affecting the female reproductive organs. CD147 (BSG) and CD98hc (SLC3A2) are oncogenes that form the CD98hc-CD147 complex, which regulates the proliferation, metastasis, metabolism, and cell cycle of cancer cells. The roles of the CD98hc-CD147 complex in ovarian cancer remain unclear. We analysed the expression and prognostic value of CD147 and CD98hc in ovarian cancer using the TCGA and ICGC databases. The effect of CD147 and CD98hc on the tumour immune response was analysed using the TIMER database. CD98hc was more highly expressed in normal tissues than primary tumour tissues, while CD147 was more highly expressed in primary tumour tissues than normal tissues. CD98hc expression was significantly associated with neutrophil and dendritic cell levels. CD147 and CD98hc were correlated with DNA repair, the cell cycle, and DNA replication. The CD98hc-CD147 complex could serve as a target for ovarian cancer treatment.